Pemerintahan Sunan Prawoto pada Masa Kesultanan Demak Tahun 1546-1549 M. - Fatimah, Nurul; Agus Widiyatmoko (FIHROS: Jurnal Sejarah dan Budaya, 2024)
Abstract The aim of this study is to analyze how Sunan Prawoto's government was during the Demak Sultanate in 1546-1549 AD. This study uses historical research methods by borrowing the cycle theory analysis tool in Ibn Khaldun's book Muqoddimah. The results of this study show that Sunan Prawoto was the fourth sultan of the Demak Sultanate. Sunan Prawoto ascended the throne amidst chaotic government conditions that were not balanced, there were threats from internal and external Demak Sultanate. To minimize bad conditions, Sunan Prawoto moved the center of government to Prawoto Hill. Sunan Prawoto has the determination to unite the island of Java under his central government with his dream of becoming the second Turkish Sultan. Keywords: Government, Sunan Prawoto, Demak Sultanate